MEMAHAMI STRUKTUR JARINGAN MEDIA SOSIAL SEBAGAI CARA STRATEGIS PERIKLANAN DI ERA EKONOMI DIGITAL - Christiany Juditha (BBPSDMP KOMINFO MAKASSAR, 2017)
Advertising in online media is now a modern business phenomenon, along with the growing e-commerce in the era of digital economy. The penetration of social media is so high provides an opportunity for manufacturers to promote products/services through social media. Still not directly drive the purchase intentions of social media users themselves to a product due to some problems that arise, among others, issues of privacy and trus and incomprehension manufacturer of the structure of social media networks make a small promotional impact. The purpose of this study was to determine the structure of social media networks as a strategic way of advertising in the era of digital economy (Instagram of Tokopedia, Traveloka, Lazada, Ayu Ting Ting, Syahrini, Riaricis and Hanggini). This study uses content analysis with qualitative approach that uses the concept of social media structures network category by Shin et al. The results showed that tie srenght, density network, centrality network, and homophile intertwined in the overall studied Instagram account when promoting a product/service. It's just that there are similarities and differences between the accounts of companies and individuals. Seventh this account has the power relationships and network congestion during the promotion process occurs. But the company accounts tend to be less receiving comments. Instead of interactions that occur tend to be higher on account of the company. The entire account owner is also a key man as the main channel of information play an important role in the network sale of product/service. The similarity of characteristics between the account owner and followers are also reflected in the promotion process.Periklanan di media online kini menjadi fenomena bisnis modern, seiring dengan tumbuh pesatnya e-commerce di era ekonomi digital. Penetrasi media sosial yang begitu tinggi juga memberikan peluang bagi produsen untuk mempromosikan produk/jasa melalui medsos. Meski demikian tidak langsung menggerakan niat beli pengguna karena beberapa masalah antara lain soal privasi dan kepercayaan juga ketidakpahaman produsen terhadap struktur jaringan media sosial membuat dampak promosi kecil. Tujuan penelitian ini adalah untuk mengetahui struktur jaringan media sosial sebagai cara strategis periklanan di era ekonomi digital (iklan di Instagram Tokopedia, Traveloka, Lazada, Ayu Ting Ting, Syahrini, Riaricis dan Hanggini). Penelitian ini menggunakan metode analisis isi dengan pendekatan kualitatif dengan konsep kategori struktur jaringan media sosial Shin dkk. Hasil penelitian menunjukkan bahwa kategori kekuatan hubungankepadatan jaringansentralitas jaringanserta kesamaan karekteristik terjalin dalam keseluruhan akun Instagram yang diteliti saat mempromosikan produk/jasa. Hanya saja ada kesamaan dan perbedaan antara akun perusahaan dan perorangan. Ketujuh akun ini memiliki kekuatan hubungan dan kepadatan jaringan pada saat proses promosi terjadi. Tetapi akun perusahaan cenderung lebih sedikit menerima komen. Sebaliknya interaksi yang terjadi cenderung lebih tinggi pada akun perusahaan. Semua pemilik akun juga merupakan orang kunci sebagai saluran utama informasiyang berperan penting dalam jaringan promosi produk/jasa. Kesamaan karekteristik antara pemilik akun dan followers juga tergambar dalam proses promosi.